Chemical and application properties of some solvent and water based coatings on wooden substrate : Kemijska svojstva i primjena premaznih materijala na bazi vode i organskih otapala na drvu - Shukla, Shikhar (Array, 2019)
Wood finishes are used extensively to improve the aesthetic value and protect wood products from moisture. These organic coatings generally contain volatile organic compounds (VOC) as solvents that evaporate when the coatings cure over the surface. Due to strict legislations against these hazardous VOCs, the buyers across the globe are shifting towards products finished with water borne coats. Two of the most commonly used wood coatings in India are polyurethane and nitrocellulose (NC) lacquer. This paper aims at comparing these two wood coatings with their water borne counterparts. The study was conducted on the wood substrate of Melia dubia. Chemical characterization of the cured coats was attempted through FTIR spectroscopy. Physical appearances in terms of gloss and film thickness were also studied. Bands of urethane, urea and nitric groups were identified, which helped in understanding the changes in chemical structure of the finishes after curing. The thickness of the organic coatings was significantly higher than that of their water-borne counterparts. Gloss of water based coatings was observed to be lesser than that of their organic solvent based counterparts in either coating material. In case of lacquer, the reduction was up-to 33 %. whereas in case of PU, gloss dropped down by about 54 %.